Prinsip-prinsip Rohani Keyakinan Kepada Kristus:: BERDASARKAN ROMA 14: 3-5 - Setiawan, Iwan; Sianipar, Yohanes; Laoli, Stephen; Putri Murcasari, Ester Nanda; Ernawati, Anik (THEOLOGIA INSANI: Jurnal Theologia, Pendidikan, dan Misiologia Integratif, 2024)
This research aims to provide a comprehensive understanding of the principles of belief in Christ based on Romans 14: 3-5 so that today's believers have an understanding of their belief in Christ. The research method used is a literature review, attempting to explain it in a hermeneutic way by interpreting the biblical text contained in Romans 14: 3-5 using reference books, and scientific articles relating to the topic of belief in Christ. The research results obtained are: First, belief in Christ makes believers live without judging each other. Second, believing that humans are accepted by God. Third, believe that there is God's presence or protection. Fourth, believers must have faith in their hearts. Belief in Christ is the only guarantee of eternal life that believers in Christ can have, belief is true belief, without the slightest doubt in it.